Classification of basic forms and types of marketing on-line communications - Yu.M. Melnik; L.Yu. Saher; N.S. Illiashenko; Yu.M. Ryazantseva (Marketing i Menedžment Innovacij, 2016)
The aim of the research. The aim of the research is to analyze objects of the marketing Internet environment, systematize and classify elements of the communication process. Research results. The article presents analysis of the main problems of marketing online communications classification. Some of them are as follows: traditional scientific and methodological approaches disregard Internet as a media resource; development of software technology and technical means of product promotion via the Internet occurs on practice prior to theoretic and methodological basis, which requires considerable time; new means and technologies of communicative impact on the target audience. Different approaches to classification of marketing online communications were analyzed. Along with traditional tools of marketing online communications (Internet Advertising, Online PR, sales promotion, direct marketing) the researchers define interactive sales, searching optimization and virtual communities, e-mail advertising, electronic bulletin boards (BBS), context (searching) advertising, media (banner) advertising, rich media, lead generation, websites sponsorship, targeting, search engine marketing (SEM), social networking optimization, social media marketing, viral internet marketing, direct Internet marketing etc. The authors defined the place of marketing online communications in the company’s communication system and proposed their own approach to their classification. The system of marketing online communications was proposed to be considered as a complex of traditional instruments that differ in means and technologies of influence: Internet advertising (media, banner, contextual, background, video, static, etc.); Public Relations (PR) («good works» on behalf of the organization or individual manager’s PR, promotional YouTube videos, etc.); sales promotions (discounts while on-line orders, discount coupons, bonuses, volume discounts, etc.); personal sales (online sales, personal communication via chats or Skype and Viber, on-line sales consultation); direct marketing (mailing list, social networks personal pages appeal etc.). Communicative Internet technologies were meant to be communication software techniques of creation of communicative messages, informational resources support and transmitting this information to target consumers on the Internet. Internet communications tools were offered to be viewed as materialized online means used to transmit communicative information to the consumer by means of Internet technologies. More over, a website was proposed to be considered as the only means of communication on the Internet, but the information (communicative message) can be presented online in various forms, hence the need to distinguish various means of Internet communications occurs: electronic media, banners, portals, Rich media, blogs, forums search engines, message boards, e-mail, articles, video blocks, files, cookies, personal pages, virtual communities and so on. Conclusions and further research. Effective use of tools of marketing online communication complex is plausible only regarding their features, understanding the technology of their impact on the target consumer – an Internet user. Such internet environment offers great opportunities for successful operation in various business (B2B and B2C). Results can form the basis of methodological approaches to selection and assessment of the effectiveness of marketing online communications, and also selection of appropriate strategies since traditional scientific and methodological approaches disregard Internet as a media resource